The Effect of Food Product and Service Quality Towards Customer Satisfaction Towards Online Satisfaction on Grab Online Application - Audrey Larisa Fortunata; Cecilia Angel Monica; Clarissa Oktavia Fondra; Crysani Mutiara; Sylvie Wilvian (MultiTech Publisher, 2021)
In line with the current advancement of information and communication technology, everything goes to the internet in any part of the world. Following the evolution of information and communication in the business world, such as purchasing and selling goods or services that are now done online (Winda Halimah, Nurdin Hidayat, & Nadya Fadillah Fidhyallah., 2021). The modern digital era has the potential to create numerous options for business success. It is also possible that culinary entrepreneurs who are now thriving in Indonesia may take advantage of this opportunity by developing online dining ordering systems in their culinary businesses. The participants in this study are active users of the Grab web application who have used the online service. Purposive sampling was utilized to identify respondents who have used the food service at least once in the previous three months. In this research we plan to describe the demographic characteristics of the participants, including age, gender, employment, and frequency of app usage. To achieve this, we intend to calculate frequencies, percentages, means, and standard deviations. These statistical measures will help provide a comprehensive understanding of the participant demographics. Frequency refers to the number of occurrences of each category within a variable